Intuitive Understanding of Kinesthetic Students in Solving Mathematics Problems with Realistic Mathematic Education Approach - Nafi'an, Muhammad Ilman; Wahyuni, Fida Ika; Afifah, Dian Septi Nur (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
Intuitive understanding is the ability to understand something without going through reasoning, so it is very important in solving math problems. One approach that can improve students' intuitive understanding is the Realistic Mathematic Education (RME) approach. However, not all students can use their intuitiveness in solving math problems. One of them is influenced by students' learning styles. For this reason, it is necessary to conduct research that aims to describe the intuitive understanding of students who have a kinesthetic learning style in solving math problems with the RME Approach. However, not all students can use their intuitiveness in solving math problems. One of them is influenced by students' learning styles. For this reason, it is necessary to conduct research that aims to describe the intuitive understanding of students who have kinesthetic learning styles in solving math problems with the RME Approach. The subjects of this research are students who have kinesthetic learning styles at SMKN 2 Tulungagung. The selection of research subjects is based on the results of the learning style questionnaire. Data collection methods with test questions, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusions.To test the validity of the data using method triangulation. Based on the research results, subject K1 leads to affirmatory intuition understanding, and subject K2 leads to anticipatory intuition understanding. It can be concluded that the intuitive understanding of kinesthetic students in solving opportunity problems has fulfilled the indicators of affirmatory intuition and anticipatory intuition. Furthermore, it is recommended to use the RME approach to improve students' intuitive understanding in solving math problems based on students' daily experiences or activities.Pemahaman intuitif merupakan kemampuan memahami sesuatu tanpa melalui penalaran, sehingga sangat penting dalam menyelesaikan masalah matematika. Salah satu pendekatan yang dapat meningkatkan pemahaman intuitif siswa adalah pendekatan Realistic Mathematic Education (RME). Namun, tidak semua siswa dapat menggunakan intuisinya dalam menyelesaikan masalah matematika. Salah satunya dipengaruhi oleh gaya belajar siswa. Untuk itu perlu dilakukan penelitian yang bertujuan untuk mendeskripsikan pemahaman intuitif siswa yang memiliki gaya belajar kinestetik dalam menyelesaikan masalah matematika dengan Pendekatan RME. Namun, tidak semua siswa dapat menggunakan intuisinya dalam menyelesaikan masalah matematika. Salah satunya dipengaruhi oleh gaya belajar siswa. Untuk itu perlu dilakukan penelitian yang bertujuan untuk mendeskripsikan pemahaman intuitif siswa yang memiliki gaya belajar kinestetik dalam menyelesaikan masalah matematika dengan Pendekatan RME. Subyek penelitian ini adalah siswa yang memiliki gaya belajar kinestetik di SMKN 2 Tulungagung. Pemilihan subjek penelitian didasarkan pada hasil angket gaya belajar. Metode pengumpulan data dengan soal tes, wawancara, dan dokumentasi. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Untuk menguji keabsahan data menggunakan triangulasi metode. Berdasarkan hasil penelitian, subjek K1 mengarah pada pemahaman intuisi afirmatif, dan subjek K2 mengarah pada pemahaman intuisi antisipatif. Dapat disimpulkan bahwa pemahaman intuitif siswa kinestetik dalam menyelesaikan masalah peluang telah memenuhi indikator intuisi afirmatif dan intuisi antisipatif. Selanjutnya disarankan untuk menggunakan pendekatan RME untuk meningkatkan pemahaman intuitif siswa dalam menyelesaikan masalah matematika berdasarkan pengalaman atau aktivitas siswa sehari-hari.